"The Poor Feel it the Most": The Antilles Bishops, the Poor, and Climate Change. (7th November 2021) - Perkins, Anna Kasafi
Abstract: This discussion examines the critical nexus that the Antilles Episcopal Conference (AEC) identifies between the poor and climate change. Attention is paid to the AEC's 2015 Declaration on Climate Change, particularly its concern with the unjust impact of climate change on the poor, poor communities, and poor countries, among which are to be found the small‐island developing nations and people of the Caribbean. Indeed, the bishops are clear that, although the negative impact of climate change is felt by various population groups, including the well‐off, "the poor feel it most." In line with Catholic social teaching, the Antilles bishops call out poverty as the result of injustice and a lack of attention to the common good. Some of the key insights of Laudato Sí treat similar concerns expressed in the repeated refrain "cry of the poor and the cry of the earth." These concerns are discussed in an attempt to deepen and challenge the AEC's thoughts while rooting its ideas squarely in the Catholic social teaching tradition. Francis's method, like that of the Antilles bishops, is marked by dialogue that takes on real problems, especially those of the poor. Francis echoes and reinforces the AEC's concern with the outsize effect of climate change and environmental destruction on the poor, which is even more urgent in the face of the COVID pandemic, which has disproportionately affected the poor in nations marked by great inequality.